Solid sampling determination of ZnO nanoparticles in eyeshadows by graphite furnace atomic absorption spectrometry - García-Mesa, Juan Carlos; Montoro-Leal, Pablo; Vereda-Alonso, Elisa Isabel; López-Guerrero, María del Mar; Siles-Cordero, María Teresa; García-de-Torres, Amparo; Cano-Pavón, José Manuel (My University, 2019)
The application of nanoparticles (NPs) in science and technology is a fast growing field. Therefore, reliable and straightforward analytical methods are required for their fast determination in different types of samples. In this work, a method that enables the determination of the average size of ZnO NPs, besides their concentration, discriminating them from ionic zinc, has been optimized. The method is based on solid sampling high-resolution continuum source electrothermal atomic absorption spectrometry (SS-HR-CS-GFAAS), and has been applied to determination and characterization of ZnO NPs in cosmetic samples. Recently, graphite furnace atomic absorption spectrometry has been introduced as a new tool to determine the size of nanoparticles by evaluation of the following parameters: atomization delay (tad) and atomization rate (kat). In this work both parameters (besides peak area) have been obtained from absorbance signals for a line of Zn with low sensitivity. Two multiple response surface designs have been used in order to optimize the adequate furnace program to achieve our aims. All the optimization experiments were performed using baby´s skin irritation protective cream. The optimized furnace program is shown in Table 1. Table 1. Optimized furnace program The size calibrations were performed against solid (powered) ZnO standards, from 50-nm to 500-nm sized nanoparticles. The correlation coefficients (R value) of the linear calibration were not worse than 0.9982. The optimized method was tested in other types of cosmetic samples such as eyeshadow samples with good results. The determination of the MNPs’ size was validated by transmission electron microscopy (TEM) and the Zn concentration in the solid samples was validated by atomic fluorescence spectroscopy (AFS). Acknowledgements (optional) [Garamond font, 10 points] The authors would like to thank Plan propio “Proyecto Puente” de la Universidad de Málaga for financial support of this work.
Keywords: Espectrometría de absorción atómica; Nanoparticulas; ZnO; solid sampling high-resolution continuum source electrothermal atomic absorption spectrometry